Real-world effectiveness, long-term safety and treatment pathway integration of radium-223 therapy in patients with metastatic castration-resistant prostate cancer - O’Sullivan, Joe M.; McKay, Rana R.; Rahbar, Kambiz; Fizazi, Karim; George, Daniel J.; Tombal, Bertrand; Schmall, Anja; Sandström, Per; Verholen, Frank; Shore, Neal (Frontiers in Medicine, 2022)
Radium-223 dichloride (223Ra) is an α-emitter approved for the treatment of metastatic castration-resistant prostate cancer (mCRPC) with bone metastases, but without visceral involvement. Despite being a life-prolonging therapy (LPT), 223Ra remains underutilized. A large body of real-world evidence (RWE) for 223Ra has been published in the decade since the pivotal phase 3 ALSYMPCA study, a period during which the treatment landscape has continued to evolve. How to optimize 223Ra use, including how to integrate it into the mCRPC management pathway amongst other current LPTs (i.e., with respect to timing and concurrent, layered, or sequential use), is therefore of considerable interest. RWE studies lack the conventional restraints of clinical trials and can therefore help to build an understanding of how treatments may be best used in routine practice. Here we review RWE studies investigating the efficacy and safety of 223Ra in mCRPC [including in sequence with the recently approved 177-Lutetium conjugated to the ligand prostate-specific membrane antigen (177Lu-PSMA)], as well as response marker development, imaging techniques, and current clinical practice recommendations.